Informational and Interpersonal Justice as Mediators Between Trasnformational Leadership and Cynicism Toward Organizational Change - Muhammad Delphino; Wustari L. Mangundjaya (Greenation Management and Business Review, 2024)
This study investigates the factors that can predict the emergence of cynicism about organizational change, which is defined as a pessimistic outlook for successful change with blame placed on "those responsible" for a lack of motivation and/or ability to effect successful change (Wanous et al., 2000). The predictor factors in this study include transformational leadership, informational justice, and interactional justice. The assessments utilized in this study were Cynicism about Organizational Change (Wanous et al., 2000), Organizational Justice Scale (Colquitt, 2001), and Multi Level Questionnaire Form 5x (Avolio et al., 1995). Respondents in this study were 165 permanent workers working in a firm that has experienced and is currently evolving, and who had been employed for at least two years. Processing data utilizing a macro process (Hayes, 2013) and a basic mediation analysis, the results show that informational justice has a mediating impact on the affects of transformational leadership on CAOC. Meanwhile, the mediating impact does not arise via interpersonal justice.